EFFECTS OF SOME FIELD PRACTICES ON THE YIELD AND QUALITY OF CASSAVA (Manihot esculenta Crantz) PLANTING MATERIAL (2011)
The use of cassava stems as planting materials is limited by scarcity, poor quality, high cost and inappropriate field techniques (land preparation, planting spacing, and field maintenance). To enhance the supply of stem for planting cassava varieties, the existing production practices were evaluated and techniques for increasing the number and quality of cassava planting materials were investigated.Seventy-four cassava farms, purposively selected in 11 major cassava growing